Right thoracotomy approach for the management of uncommon type II endoleak after thoracic endovascular aortic repair - Yoshiyuki Kobayashi, MD; Keiji Uchida, MD, PhD; Kaori Mori, MD; Kiyotaka Suzuki, MD; Aya Saito, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
An 80-year-old male with a ruptured pseudoaneurysm after aortic dissection repair underwent thoracic endovascular aneurysm repair. The aneurysm expanded from 43 mm to 89 mm over 4 years because of type II endoleak, with computed tomography angiography revealing a patent right intercostobronchial trunk and left bronchial artery on the lesser curvature of the aortic arch. These arteries were successfully dissected via right thoracotomy. During the 2-year postoperative period, the aneurysm remained stable at 80 mm. Open surgical management of the culprit vessel may be effective for type II endoleaks following thoracic endovascular aneurysm repair when endovascular approaches are challenging.